Pretreatment serum xanthophyll concentrations as predictors of head and neck cancer recurrence and survival - Arthur, Anna E. (Head Neck, 2015)
BACKGROUND: The purpose of this study was to examine associations of pretreatment serum carotenoids, tocopherols, and quercetin with prognosis in 154 newly diagnosed head and neck cancer (HNC) patients. METHODS: Pretreatment blood and health surveys were collected. Serum micronutrients were measured by HPLC. Data on recurrence and death were collected annually. Cox proportional hazards models measured associations of serum nutrient concentrations with recurrence and overall survival. RESULTS: During a median follow-up time of 37 months, there were 32 recurrences and 27 deaths. After controlling for covariates, subjects with high versus low serum xanthophyll and total carotenoid concentrations had significantly longer recurrence-free time (P = 0.002 and P = 0.02, respectively). Overall survival time was significantly longer in subjects with high versus low serum xanthophyll concentrations (P = 0.02). CONCLUSIONS: Future research should evaluate the possible benefits of interventions to increase intakes of rich food sources of xanthophylls in this patient population.